The Transparency Dilemma: Accountable on Paper, Limited in the Public Eye - Nur Avni Syamsuddin; Siti Atikah Rahayu; Hervy Sakinah; Ernawaty Usman; Abdul Kahar; Sugianto Sugianto (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This qualitative case study explores the transparency dilemma in the financial governance of Mokopido Regional General Hospital in Tolitoli Regency, where accountability is formally fulfilled but public access to information remains limited. The study examines how accountability and transparency are implemented across planning, administration, and reporting, using in-depth interviews, document review, and direct observation, including audited 2024 financial reports and relevant regulations. Findings indicate that the hospital’s accountability is supported by systematic financial processes and external auditing that resulted in a fair audit opinion, while transparency is largely confined to reporting to authorized institutions. Public access is constrained because financial and performance reports are not published through an official website or other online channels. Key barriers include manual transaction recording using spreadsheet software and limited human resource capacity, underscoring the need for digital information services, modernized financial systems, and staff capacity building to strengthen openness and timeliness.